2018 International Conference on Information Networking (ICOIN) 2018
DOI: 10.1109/icoin.2018.8343088
|View full text |Cite
|
Sign up to set email alerts
|

Trustworthiness management in sharing CDN infrastructure

Abstract: Abstract-Sharing Content Delivery Network (CDN) technologies such as CDN interconnection and cloud-based CDN have facilitated access to the huge volume of content in a cost-effective way. However, content distribution through shared CDN nodes is vulnerable to a wide variety of uncertainties, including unexpected node failure, intentional node disruption for maintenance or potential discrimination of content based on ownership. Trustworthiness can be considered as a key property to overcome the perception of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Hybrid CDN-P2P networks have recently emerged as an economically viable alternative to traditional content delivery networks. The feasibility studies conducted by several large content providers suggested a remarkable potential for hybrid CDN-P2P networks to reduce the burden of user requests on content delivery servers [12]. Subsequently, several commercial hybrid CDN-P2P networks deployments have been introduced [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid CDN-P2P networks have recently emerged as an economically viable alternative to traditional content delivery networks. The feasibility studies conducted by several large content providers suggested a remarkable potential for hybrid CDN-P2P networks to reduce the burden of user requests on content delivery servers [12]. Subsequently, several commercial hybrid CDN-P2P networks deployments have been introduced [12].…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility studies conducted by several large content providers suggested a remarkable potential for hybrid CDN-P2P networks to reduce the burden of user requests on content delivery servers [12]. Subsequently, several commercial hybrid CDN-P2P networks deployments have been introduced [12]. However, there are numerous commercial and technical challenges that negatively affect the prospects of industrial hybrid CDN-P2P solutions.…”
Section: Introductionmentioning
confidence: 99%
“…To realize this scenario, objects need to make social relationships, including policy, activities, object profile, etc. According to Reference [5], relationships between objects in SIoT can be classified as follows [18]:“co-location” relationships, established among objects used always in the same place;“co-work” relationships, established whenever objects collaborate to provide a common IoT application;“parental” relationships, related to objects belonging to the same production batch (e.g., same manufacturer, same model);“co-ownership” relationships, established among heterogeneous objects which belong to the same user.…”
Section: Introductionmentioning
confidence: 99%